PENGARUH PENAMBAHAN BEKATUL DAN TEPUNG JAGUNG PADA MEDIA TANAM TERHADAP PRODUKTIVITAS JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Anisum Anisum; Muhammad Rusdi (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2019)
The purpose of this research is to determine the composition of rice bran and corn flour which are best to planting media of while oyster mushroom and was determined of rice bran and corn flour will increase growth productivity of white oyster mushrooms. The research was conducted experimentally using Randomized Block Design (RBD) has two factors, the first factor is an addition of rice bran with treatments such as A1 = 5 kg, A2 = 1 kg, A3 = 2 kg and the second factor is an addition of corn flour with treatments such as B1 = 0.04 kg, B2 = 0.08 kg, B3 = 0.12 kg. Data analysis used Analysis of Variety (ANOVA). The results showed the highest average number of fruit bodies was 7.4 (A3B2), moreover the highest average fruit weight was 56.36 g (A3B1). However, the concluded were determined of rice bran and corn flour to planting media can increase the productivity of the growth of white oyster mushrooms with treatments A3B1, A3B2, and A3B3 can produce white oyster mushrooms up to 56.36 g. It can be concluded based the results of statistical analysis that the addition of rice bran and corn flour cannot influence the increase growth productivity of white oyster mushrooms of rice bran and corn flour will increase growth productivity of white oyster mushrooms Keywords: White oyster mushrooms, rice bran, corn flour